Contributions in Algebra and Algebraic Geometry - Dani, Shrikrishna G. (Contemporary Mathematics Ser., 2019)
This volume contains the proceedings of the International Conference on Algebra, Discrete Mathematics and Applications, held from December 9-11, 2017, at Dr. Babasaheb Ambedkar Marathwada University, Aurangabad (Maharashtra), India. Contemporary topics of research in algebra and its applications to algebraic geometry, Lie groups, algebraic combinatorics, and representation theory are covered. The articles are devoted to Leavitt path algebras, roots of elements in Lie groups, Hilbert's Nullstellensatz, mixed multiplicities of ideals, singular matrices, rings of integers, injective hulls of modu.